Gendered Wars, Gendered Memories Feminist Conversations on War, Genocide and Political Violence - Gül Altınay, Ayşe; Pető, Andrea (Taylor & Francis, 2016)
sexual; violence; gender; memory; war; genocide; conflict; militarization; feminist; creativity; women; military;